2019
DOI: 10.17520/biods.2019213
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and influencing factors of ground ant species diversity on the land-bridge islands in the Thousand Island Lake, China

Abstract: To explore spatial patterns and environmental factors affecting ground ant species diversity in the Thousand Island Lake, China, we surveyed ground ants using pitfall traps, leaf litter extraction and hand collecting on 33 islands from May to August in 2017 and 2018. We divided all ground ants into predator or omnivore ants and then used the regression models to analyze relationships between ant species diversity and island attributes. Island area had positive effects on species richness of total ants, predato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, this is not the case for β diversity conducted in island ecosystems. For example, Zhou et al found that the β diversity of ant assemblages in the Thousand Island Lake, China, was mainly contributed to by the nestedness component [52]. Similarly, nestedness also dominated the β diversity of butterfly assemblages in the Zhoushan Archipelago of China [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not the case for β diversity conducted in island ecosystems. For example, Zhou et al found that the β diversity of ant assemblages in the Thousand Island Lake, China, was mainly contributed to by the nestedness component [52]. Similarly, nestedness also dominated the β diversity of butterfly assemblages in the Zhoushan Archipelago of China [53].…”
Section: Discussionmentioning
confidence: 99%
“…The z value in the linearized power function log S = log C + z × log A was influenced by the degree of isolation to an extent. To compare z values of the SARs of bryophytes with those of other biotas, with the data of large ground‐dwelling mammals (Xu et al, 2014), small mammals (Wang et al, 2010; Zhao et al, 2009), birds (Ding et al, 2013), lizards (Hu et al, 2012), spiders (Ge, 2015), ants (Zhou et al, 2019), and vascular plants (Hu et al, 2011) in TIL, we modeled the SARs of bryophytes and the above biotas with the same area unit (m 2 ).…”
Section: Methodsmentioning
confidence: 99%